Swing it, Sunny! - Holm, Jennifer L.; Holm, Matthew (New York : Graphix, 2017)
In the mid-1970s Sunny Lewin is back, star of her personal show, facing the prospect of Middle School, and dealing with the problems of her somewhat dysfunctional family--in particular her older brother, Dale, who has been sent off to a military academy because of his delinquent behavior.
School Library Journal starred, August 2017
Kirkus Starred, July 2017
Booklist, July 2017
2.9
3-6
GN480L
Keywords: Family problems -- Fiction; Brothers and sisters -- Fiction; Middle schools -- Fiction; Schools -- Fiction; Family life -- Comic books, strips, etc. -- Fiction; Middle schools -- Comic books, strips, etc. -- Fiction; School stories; Siblings -- Comic books, strips, etc. -- Fiction; Graphic novels